Urbanization and Its Impact on Urban Poor Housing Policies Based on Some Experiences of Third World Countries - Al-Dhabhani, Bilal Redman Ali; Al-Madhaji, Mohammed Ahmed Sallam (University of Science and Technology, Yemen, 2018)
Many third world countries have experienced a process of rapid urbanization. The rapid rural-urban migration and the lack of proactive planning have resulted in the expansion of slums and squatter settlements inhabited by low-income and the poor, excessive house rents and poor or total absence of infrastructural facilities. The problem more recently exacerbated in most cities of the third world as a result of the failure of governments to respond adequately to the urban development challenges by adopting adequate housing policies to the urban poor. This paper focuses on the study of urbanization and the impact of poverty and deprived urban living conditions on urban areas. It aims to find out the correlation between the poor urban areas and the housing policies, pinpoints the most successful housing policies to be taken to provide an adequate environment, and proposes basic guidelines for housing policies of the poor in the countries of the third world.